Dalyvavimas internete: politiškai aktyvus jaunimas ir jo komunikacija socialinėse medijose - Auškalnienė, Lina (Information & Media, 2012)
Informacijos ir komunikacijos technologijų plėtra yra viena pagrindinių charakteristikų, apibūdinančių socialinius, kultūrinius, ekonominius XXI a. demokratijos procesus. Fundamentalūs kaitos procesai veikia ir politikos komunikacijos sritį – neišvengiama pokyčių, įsitraukia nauji veikėjai, naudojami nauji įrankiai, kinta komunikacijos įpročiai. Šio straipsnio tikslas – apžvelgti literatūrą, kurioje nagrinėjami iššūkiai bei galimybės, siejamos su piliečių įsitraukimo bei politinio dalyvavimo praktikomis socialiniais tinklais ir ryšiais grindžiamoje virtualiojoje erdvėje. Straipsnyje taip pat pristatomas bandomasis tyrimas, analizuojantis politiškai aktyvių jaunų žmonių demokratinio įsitraukimo praktikas socialinėse medijose. Keliami klausimai aktualūs ir ateities tyrimams bei diskusijoms: ar socialinės medijos galėtų tapti patraukliu kanalu, prisidedančiu aktyvinant jaunų auditorijų politinio bei pilietinio dalyvavimo praktikas?Assessing participation online: Youth and Their Involvement in Social MediaLina AuškalnienėSummaryThe role of political participation and civic engagement as the backbones of modern deliberative democracy is challenged by new opportunities for involvement online. Fundamental societal transformations, facilitated by new technologies, are changing the way we interact, communicate, produce and exchange knowledge. By nature being a bottom-up experiment, social media are more and more involved into the everyday communication practice and become one of the major political communication channels.The purpose of this paper is to review the literature analysing the democratic citizens’ engagement and political participation in the era of the Internet, particularly focusing on the involvement of young people in the decision-making process. Moreover, a pilot case study is presented, reflecting the practices of politically active young individuals in the online communicative space. The data available are analysed to shed some light on the debate and to focus attention on several aspects of youth participation. Looking further, the questions are raised: is the Internet an attractive channel to enhance political interest and discussion among the youngsters? What impact may online communication practice via social media have on civic and political participation of young people offline?Key words: social media, political participation, democratic engagement, political communication, Internet, youth